2009
DOI: 10.5539/jsd.v1n1p58
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and the Distortion of Technology Transfer and Marketing Processes: An Insight into Africa’ Economic Malaise and the Decadence of Its Social Fabric

Abstract: Corruption is an economic and social cancer afflicting industry and society at large the world over and is a major drawback to economic and social prosperity. It is the contention of this paper that corruption is a devastating form of social and economic injustice that has devastated the prospects for the dark continent of Africa. The root cause of corruption is the greediness of the leadership. Unfortunately corruption breeds corruption across the social divide as the leadership seeks to consolidate and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The increment in ethical misconduct will see a weighty decrease in the nature of project performance as prove by measurements from the construction related journals. Kadembo (2008), featured that unethical and corrupt practices have a considerable measure of unfavorable impact on the construction industry, including the advancement of the economy and human resources. Unscrupulous or unethical practices has a tendency to misshape construction process and along these lines hamper economic fortune.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increment in ethical misconduct will see a weighty decrease in the nature of project performance as prove by measurements from the construction related journals. Kadembo (2008), featured that unethical and corrupt practices have a considerable measure of unfavorable impact on the construction industry, including the advancement of the economy and human resources. Unscrupulous or unethical practices has a tendency to misshape construction process and along these lines hamper economic fortune.…”
mentioning
confidence: 99%
“…Unscrupulous or unethical practices has a tendency to misshape construction process and along these lines hamper economic fortune. Unethical performance obstructs the free play of market powers in the industry, demoralize financial aid from the outside benefactors /foreign donors and it makes relatively difficult to pull in and global investors disregard the degenerate conditions to the burden of the economies (Kadembo, 2008). A review of construction industry ethical practices in the USA directed by FMI in conjunction with the Construction Administration Relationship of America (FMI/ CMAA, 2004) found that, in 2003, 84% of the responding building owners, architects, A/E firms, construction managers, contractors and subcontractors had encountered, experienced or watched construction industry-related acts or transactions that they would consider unethical.…”
mentioning
confidence: 99%
“…Unethical or corrupt practices tends to distort construction process and thereby hamper economic fortune. Unethical performance hinders the free play of market forces, discourage economic aid from the foreign donors and it makes almost impossible to attract and international investors shun the corrupt environments to the detriment of the economies and communities of the respective countries (Kadembo, 2008) Bribery and corruption are taken by many Nigerians as norm even in the face of anti-corruption crusades intended to support clean governance. Goldstock (1990) pointed out that a consequences of corruption is that it dramatically increases the cost of construction by undermining corruption for instance, corruption on residential projects eliminates both middle-and -low-income housing.…”
Section: Effects Of Unethical Behaviour and Conduct On The Industrymentioning
confidence: 99%
“…The ranking by CPI was based on acceptance of bribes and misuse of post by elite politicians and government officials to achieve their selfish goal. Kadembo (2008) posited that very few powerful politician rarely get prosecuted for crimes such as corruption, extortion and bribery or the use of public offices for personal benefit most especially in developing countries because the system of governance protects them. Kadembo (2008) further explained that there are double standard of laws being applied in most developing nations of the world -one for the political leaders and their cronies and the other for the poor and defenseless masses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation